Evaluation of the Drumband Extracurricular Program Using the CIPP Model Based on School Management Stages at SD Negeri 2 Kedungjati - Setyawan, Rafli; Sanoto, Herry (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to evaluate the drumband extracurricular program at SD Negeri 2 Kedungjati using the CIPP (Context, Input, Process, Product) evaluation model, which is integrated with the stages of school management. The CIPP model was chosen because it provides a comprehensive overview of program implementation, starting from planning, execution, to the outcomes achieved. This research employed a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, documentation, and data triangulation. The results show that in terms of context, the drumband extracurricular program aligns with students’ needs and supports the school’s vision and mission. From the input aspect, the program is supported by competent trainers and supervising teachers, although some limitations in facilities and infrastructure still exist. The process aspect indicates that the activities are carried out in a structured manner and receive support from various parties. In terms of product, the program has had a positive impact on students, especially in fostering discipline, self-confidence, and teamwork skills. Although the program has not yet achieved success in formal competitions, students’ participation in community events serves as an added value. Overall, the drumband extracurricular program has contributed positively to the character development of students. The findings of this evaluation are expected to serve as a consideration in developing more effective and sustainable extracurricular programs in the future.